Asthimajjagata Vatamanagement - Avascular Necrosis (AVN) Through Majjabasti and Shaman Chikitsa- A Case Study: Life Sciences - Dodiya, Dr. Mahesh; Parwe, Shweta; Nisargandha, Milind; Sawarkar, Punam (International Journal of Life Science and Pharma Research, 2023)
In clinical practice, the number of Avascular Necrosis cases is increasing due to lifestyle changes, heavy workload, degenerative changes, and improper dietary habits. It is a progressive degenerative condition of the hip joint due to a lack of blood supply to the bone. Modern practice shows a significantly lower prognosis as per the studies. With the help of cardinal features of the AVN (Avascular Necrosis), it may correlate with Ashthi Majjagata Vikarain Ayurveda. Vata Vyadhi can treat at the clinical level with the help of AyurvedicShamana(palliative treatment) and ShodhanaChikitsa(Purification treatment). According to Ayurveda Acharyas, the Basti karma is the best line of treatment in Vata Vyadhi and is also called Ardha-Chikitsa. Ayurvedic Treatment gives long-term relief from the disease, helps to enhance the inner strength of the body tissues, and stops the progression. A 36-year-old male patient complained of Breaking Pain in the femur bone, Pain in the right hip joint, difficulty walking, and radiating Pain from the lumbar to thigh region. Associated with restricted movement of the right leg and disturbed sleep. He was treated with ShamanaAushadhis, followed by Abhyanga, Swedana, and Majjabasti with the combination of Majja(goat bone marrow) and GoKsheerfor12days. The patient was assessed withM.R.I. and grading of the symptoms; significant changes and improvements were observed in symptoms before and after the treatment. This study has been conducted to evaluate the efficacy of Majjabasti in managingAsthimajjagata Vatavikar based on Ayurvedic management. It shows that Majjabasti can be used in clinical practice for managing AVN, along with all precautionary measures described in Ayurveda classics in the form of PariharaVishayas during Bastikarma should be followed.